TEACHERS' EXPERIENCES ON THE BLOOKET APPLICATION AS A LEARNING TOOL IN THE ENGLISH LANGUAGE - Nazry Nasyifa; Diah Safithri Armin (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study aimed to explore English teachers’ perspectives on using the Blooket application as a digital learning tool in a junior high school context in Medan, Indonesia. In response to the growing emphasis on gamification in education, particularly in language learning, the study sought to understand how game-based platforms such as Blooket are implemented and perceived by educators. Using a qualitative case study approach, data were collected through semi-structured interviews with three English teachers whose teaching experience ranged from two to ten years. Thematic analysis was employed to examine the data. The findings revealed that teachers were primarily motivated to use Blooket due to its perceived ability to increase student engagement and improve vocabulary acquisition. Additionally, the platform positively influenced classroom dynamics by encouraging active participation and fostering a more inclusive learning environment. Despite these benefits, teachers also reported several challenges, such as unstable internet connectivity and the difficulty of aligning gamified content with curriculum objectives. These experiences reflect the need for thoughtful integration of gamification strategies alongside pedagogical goals. Grounded in principles of constructivist and behaviourist learning theories, the study highlights the potential of Blooket as a supplementary instructional tool when supported by sufficient technological infrastructure and reflective teaching practices. However, as a small-scale study, these findings are context-specific and should be interpreted with caution. Future research is recommended to include a broader participant sample and to compare the use of different gamified platforms across varied educational settings to further assess their impact on language learning.